The Students’ Attitude towards the Using of Dictation Strategy in Improving Students’ Listening Skills - Arif Triyuono; Agustina Ramadhianti (Sean Institute, 2026)
Listening is a fundamental language skill that plays a crucial role in English as a Foreign Language (EFL) learning. However, many students encounter difficulties in comprehending spoken English due to limited vocabulary, unfamiliar pronunciation, and varying speech rates. Dictation has been widely recognized as a learning strategy that integrates listening, memory, and writing skills to enhance listening comprehension. This study aimed to investigate students' attitudes toward the use of the dictation strategy in improving their listening skills. A descriptive survey design was employed involving 80 undergraduate students enrolled in the English Education Program. Data were collected using a structured questionnaire consisting of 20 Likert-scale items and analyzed descriptively using percentage analysis. The findings indicate that students generally have positive attitudes toward the implementation of dictation. Approximately 87.1% of the respondents agreed that dictation effectively improved their listening skills. In addition, students perceived that the strategy enhanced vocabulary acquisition, pronunciation, spelling accuracy, and comprehension of different English accents. Despite reporting several challenges, particularly the difficulty of the tasks, most participants acknowledged that the educational benefits outweighed the limitations. These findings suggest that dictation is an effective pedagogical strategy for fostering listening comprehension and can be integrated into English language instruction to promote more active and meaningful learning experiences